A new species of Mancoa (Brassicaceae), endemic to Michoacán, Mexico - Hernández-Sandoval, Luis; Martínez, Mahinda (Instituto de Ecología, A.C., 2013)
Mancoa perennis, a new species endemic to Michoacán, Mexico is described and illustrated. The new species is similar to M. laxa, but differs in its perennial habit, the caulinar leaf lobes ovate or triangular, entire, apically bearing a branched trichome, and a dense inflorescence with glabrous pedicels.